Post-operative analgesia techniques after total knee arthroplasty: A narrative review - G V Krishna Prasad (Saudi Journal of Anaesthesia, 2020)
Post-operative knee pain management has become a challenge to provide early relief and pain-free postoperative care to the patient. The major objectives of post-operative analgesic treatment are to reduce opioid requirements, post-operative pain, and adverse events related to opioid intake. This narrative review aimed to document post-operative analgesia techniques after total knee arthroplasty (TKA). The traditional approach involved high-dose opioid-based regimen, though opioid is considered strong analgesic, but are associated with a number of unwanted side effects to seek for alternative techniques. The role of sciatic nerve block in TKA pain is doubtful. Femoral Nerve Block (FNB) is still considered as the gold standard; however, FNB is associated with quadriceps weakness and risk of fall and sciatic block with foot drop. To overcome these drawback more distal nerve block techniques has evolved, namely saphenous nerve block in adductor canal, selective tibial which are claimed to provide comparable analgesia to that of femoral and sciatic nerve block. The combination of pre-emptive and multi-modal analgesia and technically well-delivered regional nerve blocks and postoperative physical therapy are an essential component which not only minimize the side effects of traditional opioid-based analgesia but also speed up functional recovery, increases patient satisfaction, and reduces the overall length of hospitalization and cost.